Development of Extruded Ready-To-Eat Snacks from Purple Rice - Fakfoung, S. (International Journal of Agricultural Technology, 2018)
The objective of this study was to investigate optimum diets for extruded snacks made from purple rice. The study was performed using a simplex-lattice mixture design. The range of three ingredients was 60-70% purple rice, 12-22% corn flour and 13-23% water equivalent for a total of 100%. Data was analyzed using ANOVA; while response surface analysis was generated using the Scheffe’s second degree polynomial. Results showed that changes in percentages of the three components significantly affected (p£0.05) sensory and physicochemical properties. Predictive models were used to plot the contour line of all sensory attributes with acceptability score greater than 5.0 being selected as optimum. Resulting overlayed contour plots indicated the most ideal diet was 70% purple rice, 12% corn flour and 18% water. Instrumental texture properties for optimum extruded snacks were composed of lightness (L*) 17.09, redness (a*) 3.09 yellowness (b*) 5.38, moisture 0.79%, water activity (aw) 0.61%, texture hardness 5.76 N. The selected diet had average score, appearance, color, flavor and overall acceptance (n = 250) in moderate levels.